Recovery of humic-like susbtances from low quality composts - Olga C. Nunes (2013)
The quality of four commercial composts produced from poultry litter and municipal solid wastes was assessed based on their physic-chemical, stability and maturity parameters. These properties varied among the analysed composts; it was found that electric conductivity, heavy metals content and maturity were the parameters that limited the composts quality. Therefore, the feasibility of using them to obtain liquid fertilisers rich in humic-like substances (HS) was assessed. The HS yield, phytotoxicity, heavy metals co-extraction and chemical characterization were carried out. The linkage of the HS chemical composition with the compost properties was assessed by multivariate analysis. Among the compost properties, germination indices, Cr and Cu contents were the parameters that correlated most with the HS chemical composition. The low levels of metals and absence of phytotoxicity in all the analysed HS extracts indicate that composts with low quality may be used to produce liquid organic fertilisers, substituting those from natural resources. (C) 2012 Elsevier Ltd. All rights reserved.